An Analysis of Human Capital Development in Indonesian Islamic Banking System - Sayakhmad, Olimov; Said, Muhammad; Rini, Rini (Tapis: Jurnal Penelitian Ilmiah, 2022)
The present study aim was to analyze human capital development in Indonesian Islamic banking sector, and mainly this study discussed the potential of Islamic banks employee’s knowledge and skills improvement for strengthening their competitive advantages. The following research used qualitive analysis method with primary data collection in the form of semi – structured interviewing of HR manager’s Islamic banks in Indonesia. The result and discussion of present study indicated that indeed, Islamic banks in Indonesia need to strengthen their competitive advantages by delivering an effective training to improve employee’s competency. As mentioned, the finding of study indicated that Islamic banks have to invest more on human capital development as source of business value creation for increasing workforce productivity. In addition, the finding of this study contributes for further research to discuss the contemporary issue of human capital development in Islamic banking industry.